The Effect Of Differentiated Instruction On Eleventh Grade Students' Narrative Writing Skill At SMA Budi Murni 2 - Maria Sihotang; Meikardo Samuel Prayuda; Fiber Yun Almanda Ginting (Pengertian: Jurnal Pendidikan Indonesia (PJPI), 2026)
This study aims to analyze the effect of Differentiated Instruction on the narrative text writing ability of grade XI students of SMA Budi Murni 2 in the 2025/2026 academic year. This study is motivated by the low ability of students in developing story ideas, organizing plots coherently, using appropriate vocabulary and grammar, and constructing narrative text structures as a whole. In addition, differences in students' abilities, interests, and learning readiness cause the writing learning process to not run optimally. This study used a quantitative method with a quasi-experimental design involving an experimental class and a control class. Data were obtained through pre-tests and post-tests of narrative text writing ability, then analyzed using statistical tests to determine differences in learning outcomes between the two groups. The results showed that students taught through Differentiated Instruction achieved higher writing ability improvements than students taught using conventional methods. The average score of the experimental class increased from 61.94 to 76.39, while the control class increased from 58.19 to 66.39. The results of the Independent Samples T-Test showed a significance value of 0.000, which is smaller than 0.05. Therefore, it can be concluded that Differentiated Instruction has a significant influence on students' narrative writing skills. Thus, this strategy can be an effective learning alternative in helping students improve their writing skills according to their learning needs and characteristics.